THE ADMINISTRATIVE RESTRUCTURING ON MEXICO’S EDUCATION REFORM - Orta Martínez, Ma. Esther (Atenas, 2015)
This article offers an analysis, from the point of view of administrative law, of one aspect of Mexico’s education reform, supported by the amendment to Article 3 of the Political Constitution of the United States of Mexico, which led to the creation of the National Institute for the Evaluation of Education as an autonomous and public body with legal personality and assets of its own, which will assist in the implementation of a process targeted on improving the quality of education as the basis for strengthening the national education system. This will be achieved by the due process of evaluating teachers, detecting and addressing training needs, which will promote the efficiency of the enactment of the education reform in order to optimize teaching, leadership and school management, given the alarming results extracted from self-appointed evaluation procedures as well as assessments executed by international organizations about the quality of education in our country and its repercussion on society, taking in account the increasing rates of poverty, marginalization and crime.